MicroRNAs Used in Combination with Anti-Cancer Treatments Can Enhance Therapy Efficacy - Mognato, Maddalena; Celotti, Lucia (Mini Reviews in Medicinal Chemistry, 2015)
MicroRNAs (miRNAs), a recently discovered class of small non-coding RNAs, constitute a promising approach to anti-cancer treatments when they are used in combination with other agents. MiRNAs are evolutionarily conserved non-coding RNAs that negatively regulate gene expression by binding to the complementary sequence in the 3’-untranslated region (UTR) of target genes. MiRNAs typically suppress gene expression by direct association with target transcripts, thus decreasing the expression levels of target proteins. The delivery to cells of synthetic miRNAs that mimic endogenous miRNA targeting genes involved in the DNA-Damage Response (DDR) can perturb the process, making cells more sensitive to chemotherapy or radiotherapy. This review examines how cells respond to combined therapy and it provides insights into the role of miRNAs in targeting the DDR repair pathway when they are used in combination with chemical compounds or ionizing radiation to enhance cellular sensitivity to treatments.
Keywords: Cell cycle checkpoints